Synthesis and properties of 3-(ethylthio)-9-methyl-6-(alkylthio)pyrazolo[1,5-d][1,2,4]triazolo[3,4-f][1,2,4]triazines - S. O. Fedotov; A. S. Hotsulia (Zaporozhye State Medical University, 2022)
The combination of pyrazole and 1,2,4-triazole fragments in one structure makes it possible to achieve some success in creating potential biologically active compounds. Various factors contribute to this process. Among them, we can note the significant possibilities of chemical transformation involving these cycles, the simplicity, and reliability of methods, the creation of molecules with a certain level of bioavailability and the ability to influence a number of biochemical processes. Taking into account the presented facts, the creation of new compounds in a number of pyrazolo-triazole condensed systems is scientifically attractive with endowed features of practical significance and relevance. The aim of the work was to identify optimal conditions for the production of 3-(ethylthio)-9-methyl-6-(alkylthio)pyrazolo[1,5-d][1,2,4]triazolo[3,4-f][1,2,4]triazines and to study the properties of the target reaction products. Materials and methods. The chemical part of the work involved the step-by-step creation of target reaction products in the form of 3-(ethylthio)-9-methyl-6-(alkylthio)pyrazolo[1,5-d][1,2,4]triazolo[3,4-f][1,2,4]triazines. The first stage was aimed at conducting the interaction of diethyloxalate with acetone with the participation of sodium methylate in a methanol medium. Ethyl-2,4-dioxopentanoate was used in the conversion process to 3-methylpyrazole-5-carbohydrazide with the participation of hydrazine hydrate. Further modification of the molecule consisted of the gradual formation of the structure of 4-amino-5-(3-methylpyrazol-5-yl)-1,2,4-triazole-3-thiol. The next step involved the synthesis of 3-ethylthio-5-(3-methylpyrazol-5-yl)-1,2,4-triazole-4-amine. Further conversion included the production of potassium 3-ethylthio-9-methylpyrazolo[1,5-d][1,2,4]triazolo[3,4-f][1,2,4]triazine-6-thiolate and its S-alkyl derivatives along the triazine fragment. Cyclooxygenase-2, lanosterol-14α-demethylase and receptor tyrosine kinase were selected as model enzymes for docking, the crystal structure of which was loaded from the Protein Data Bank. Results. The synthesis of 3-(ethylthio)-9-methyl-6-(alkylthio)-pyrazolo[1,5-d][1,2,4]triazolo[3,4-f][1,2,4]triazines were carried out and the optimal conditions for the production of these substances were determined. The structure of the chemical transformation products was proved and the results of the study of the main physical properties were recorded. The results of virtual studies provided an opportunity to substantiate the prospects of the selected chemical transformation vector, which ultimately made it possible to determine the biological potential of the obtained compounds. Conclusions. Based on the results of the study, information was obtained that gives a certain idea of the possible level of influence of synthesized compounds on the activity of lanosterol-14α-demethylase, which makes it advisable to further search for substances with fungistatic and fungicidal effects.